An Encounter with a Worm in Anterior Chamber: A Case Report - Pradhan, Deepti; Pradhan, Chandni; Joshi, Purushottam (Nepalese Journal of Ophthalmology, 2018)
Background: Several parasites are known to affect the eyes, some of them even causing blindness. Data on helminths infecting the eye are scant and mostly limited to case reports from different countries. Case: A 53 years old female presented with complaint of redness, foreign body sensation and diminution of vision in right eye since one month. Observations: On examination a live motile worm was found wriggling in the anterior chamber which was surgically removed. The microscopic findings were in favour of Dirofilaria. However, detailed histopathological examination and determination of species couldn’t be done. Conclusion: The occurrence of parasite in eye is an uncommon event. Most of these parasites are found in subconjunctival or subretinal regions. Those in anterior chamber is a very rare event. Recently Dirofilaria is being recognised as an emerging zoonosis.